Smoking behaviors in a community-based cohort of HIV-infected indigent adults - Vijayaraghavan, Maya (2014)
We conducted a longitudinal study of a community-based cohort of HIV-infected indigent adults to examine smoking behaviors and factors associated with quitting. We assessed “hardcore” smoking behaviors associated with a low probability of quitting. Of the 296 participants, 218 were current smokers (73.6%). The prevalence of “hardcore” smoking was high: 59.6% smoked ≥ 15 cigarettes per day, and 67.3% were daily smokers. During the study interval, 20.6% made at least one quit attempt. Of these, 53.3% were abstinent at 6 months. The successful quit rate over two years was 4.6%. Illegal substance use (adjusted odds ratio, AOR 0.2, 95% CI 0.1-0.6) and smoking within 30 minutes of waking (AOR 0.2, 95% CI 0.1-0.7) were associated with lower likelihood of making a quit attempt. Interventions that reduce nicotine dependence prior to smoking cessation and those that are integrated with substance use treatment may be effective for this population.